Investigation of the effect of Equivac® HeV Hendra virus vaccination on Thoroughbred racing performance. Issue 4 (4th February 2018) - Schemann, K; Annand, EJ; Reid, PA; Lenz, MF; Thomson, PC; Dhand, NK
Abstract : Objective: To evaluate the effect of Equivac® HeV Hendra virus vaccine on Thoroughbred racing performance. Design: Retrospective pre‐post intervention study. Methods: Thoroughbreds with at least one start at one of six major south‐eastern Queensland race tracks between 1 July 2012 and 31 December 2016 and with starts in the 3‐month periods before and after Hendra virus vaccinations were identified. Piecewise linear mixed models compared the trends in 'Timeform rating' and 'margin to winner' before and after initial Hendra virus vaccination. Generalised linear mixed models similarly compared the odds of 'winning', 'placing' (1st–3rd) and 'winning any prize money'. Timeform rating trends were also compared before and after the second and subsequent vaccinations. Results: Analysis of data from 4208 race starts by 755 horses revealed no significant difference in performance in the 3 months before versus 3 months after initial Hendra vaccination for Timeform rating (P = 0.32), 'Margin to winner' (P = 0.45), prize money won (P = 0.25), wins (P = 0.64) or placings (P = 0.77). Further analysis for Timeform rating for 7844 race starts by 928 horses failed to identify any significant change in Timeform rating trends before versus after the second and subsequent vaccinations (P = 0.16) or any evidence of a cumulative effect for the number of vaccines received (P = 0.22). Conclusion: No evidence of an effect of Hendra virus vaccination on racing performance was found. The findings allow owners, trainers, industry regulators and animal health authorities to make informed decisions about vaccination.